Sociodemographic and health factors associated with the risk of financial catastrophe when informal care for patients with haematological neoplasms is replaced by formal care - Raúl del Pozo-Rubio; Marta Ortega-Ortega (Health Economics Review, 2022)
Background: Cancer is one of the diseases with the highest incidence and mortality in the world, and one that requires greater care (formal and informal). At present, the traditional informal caregiver is disappearing. The objective is to analyse the sociodemographic and health factors associated with the possible catastrophic financial effect on households of replacing informal care by formal care for patients with blood cancer, during the different stages of treatment in Spain. Methods: A total of 139 patients with haematological neoplasm who underwent stem cell transplantation completed a longitudinal questionnaire during each of three treatment phases. Of this population, 88.49% received informal care. The households were classified into those where the replacement of informal care with formal care would impose a financial burden exceeding 40% of equivalent household income, versus those who would not suffer this consequence. Three logistic regression models (one for each treatment phase) were estimated and the corresponding marginal effects determined. Results: The factors associated with a higher probability of financial catastrophe were married marital status, low education level, fair to very poor self-perceived health status, the diagnosis of leukaemia in the pre-transplant and first-year post-transplant phases and of multiple myeloma disease in the final post-transplant phase. Conclusions: These findings reveal the need to design social policies to meet the care needs of patients with blood cancer which at present are covered by informal care. Given the foreseeable elimination of this option, these families must be protected from the financial burden incurred from the use of privately-contracted assistance.
Keywords: D63; I0; I38; 330; Informal care; Formal care; Haematologic neoplasms; Financial catastrophe